Application of Smart City Construction in a New Data Environment - Zhao, Yunhong; Li, Suruo; Chen, Huafeng; Xu, Yuhua (Frontiers in Energy Research, 2022)
With the rapid development of Internet, cloud computing, Internet of things, mobile Internet and other information technologies, big data technology is widely used in all aspects of smart city construction. This paper analyzes the development status of big data in urban planning and construction, and studies the application of big data technology in smart city construction. This paper mainly analyzes and studies from the aspects of smart city planning, smart transportation, smart community, smart health care and smart education, and finally puts forward relevant thoughts.